2013
DOI: 10.1039/c3tc31235f
|View full text |Cite
|
Sign up to set email alerts
|

Correlating molecular morphology with optoelectronic function in solar cells based on low band-gap copolymer:fullerene blends

Abstract: We review recent progress in the development of organic bulk heterojunction (BHJ) solar cells employing donor-acceptor copolymers as the electron-donor and fullerene derivatives as the electron-acceptor. We discuss the role of the donor and acceptor moieties, side-chains, bridging units and atomic substitutions of the copolymers on their optoelectronic functionality. The physical properties, e.g. molecular conformation, miscibility, phase-separated lateral and vertical morphology, of various photovoltaic blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 190 publications
(277 reference statements)
3
55
0
Order By: Relevance
“…[ 2,3 ] This morphology has been typically achieved by the manipulation of coating conditions, after processing thermal or solvent annealing and by the choice of solvent and processing additives. [ 2,3 ] In many cases, the nanostructure of the blend can be considered kinetically trapped rather than thermodynamically preferred.…”
Section: Doi: 101002/aenm201401228mentioning
confidence: 99%
“…[ 2,3 ] This morphology has been typically achieved by the manipulation of coating conditions, after processing thermal or solvent annealing and by the choice of solvent and processing additives. [ 2,3 ] In many cases, the nanostructure of the blend can be considered kinetically trapped rather than thermodynamically preferred.…”
Section: Doi: 101002/aenm201401228mentioning
confidence: 99%
“…This result denotes that the HOMO energy levels of the designed SMs 2-5, having more coplanar configuration across the backbone than 1, are very close to the HOMO energy of an ideal polymer (~-5.4 eV), providing them with good long-term stability in air and their BHJ photovoltaic devices with high V OC [32,57]. However, the LUMO energy levels of the molecules 2-5 are between -3.40 eV and -3.57 eV, lower by about 0.26 to 0.39 eV than that of 1.…”
Section: Computational Detailsmentioning
confidence: 67%
“…Previous studies have demonstrated that the crystalline character of BDT based D-A copolymers and SMs can be adjusted by increasing the number of nitrogen atoms in the acceptor unit [32,33]. Benefited from the good properties of SM 2, we have subsequently designed SMs 3 and 4 by retaining the core acceptor unit of 2 and modifying the core donor BDTT-S by substituting some carbon atoms by nitrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…While using donor-fullerene dyads as single active components provides excellent excitons dissociation yields, it also limits the interface between donating and accepting domains to the molecular size, leading to low overall efficiency. In fact, fullerene-based photovoltaic devices do not use molecular dyads as active material, but rather rely on fullerenecontaining polymer blends to enhance electron and hole transport to opposite electrodes by means of a bi-continuous interpenetrating network [198], leading to what is known as heterojunction polymer solar cells. The conjugated polymers act as electron donors, and functionalized fullerenes such as methanofullerenes and indene-fullerene derivatives [181,199,200,201] as acceptor molecules: after creation of excitons by absorption of light, they are separated by electron transfer from the donor's LUMO to the lower-lying fullerene LUMO.…”
Section: D2 Optoelectronic Properties Of Fullerene Derivatives Withmentioning
confidence: 99%